PERAN KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN PERILAKU ORGANISASI SEKOLAH - Mustaidah; Noor Miyono; Siti Mukhayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the role of principals in enhancing school organizational behavior focused on student achievement at SMA N 1 Belik. Using a qualitative descriptive method, data were collected through observation, in-depth interviews, and documentation. The findings reveal that principals play a key role in fostering a supportive organizational culture for student success. By implementing effective leadership—strategic vision, motivational skills, and transformational approaches—the principal mobilizes school elements to achieve shared goals. Positive organizational behavior, such as teamwork, discipline, and focus on student potential development, significantly impacts academic and non-academic success. Strengthening communication between junior and senior teachers, promoting interactive learning methods, encouraging student participation in extracurricular activities, and providing training programs for self-development are among the suggested strategies to enhance school organizational behavior.